Integrating the Colon Leakage Score (CLS) and Serum Albumin to Predict Anastomotic Leakage in Colorectal Cancer Surgery: A Diagnostic Accuracy Study in an Indonesian Cohort - Muhammad Rizqi Firyal; Muhammad Hafidh Komar; Theodorus (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Anastomotic leakage (AL) is a devastating complication in colorectal surgery, associated with high rates of morbidity and mortality. Accurate preoperative risk stratification is essential for guiding clinical decision-making. This study aimed to evaluate the diagnostic accuracy of a synergistic model combining the clinical Colon Leakage Score (CLS) with the biochemical marker of preoperative serum albumin for predicting AL in an Indonesian patient cohort. Methods: A retrospective diagnostic accuracy study was conducted at a single tertiary care center. The study included 60 patients who underwent resection and primary anastomosis for colorectal cancer between January 2022 and June 2024. Patients who received a diverting stoma were excluded. A